Design and Analysis of a Compact Dual-Band Wearable Antenna for WBAN Applications - MUSA, UMAR; MOHD SHAH, SHAHARIL; A. MAJID, HUDA; MAHADI, ISMAIL AHMAD; A. RAHIM, MOHAMAD KAMAL; YAHYA, MUHAMMAD SANI; ZAINAL ABIDIN, ZUHAIRIAH (Ieee Acces, 2023)
The design and analysis of a compact dual-band wearable antenna for WBAN applications is presented. The antenna was prototyped on a semi-flexible Rogers Duroid RO3003™ with compact dimensions of 41 × 44 mm2 which corresponds to 0.33 λ0 × 0.35 λ0, where λ0 is the free space wavelength at 2.4 GHz. The antenna is designed in the preliminary stage to resonate at 5.8 GHz. An inverted U-shaped slot is added to the patch to create one more resonant frequency at 2.4 GHz. To enhance the antenna’s bandwidth and gain, two slots at the patch’s bottom edge and a partial ground are added. The measured percentage of impedance bandwidth at 2.4 GHz and 5.8 GHz are 3.75% and 5.17%, respectively. The gain is measured to be 3.74 dBi and 5.13 dBi and the efficiency is 91.4% and 92.3%, respectively at the operating bands. The measured radiation patterns exhibit a bidirectional and directional radiation pattern in the E-plane at 2.4 GHz and 5.8 GHz bands, while omnidirectional radiation patterns are observed in the H-plane. At 2.4 GHz, the SAR limits are simulated to be 0.955 W/kg and 0.571 W/kg for 1 g and 10 g of human tissue, while at 5.8 GHz, the SAR limits are 0.478 W/kg and 0.127 W/kg, respectively. Therefore, the proposed antenna has met the FCC and ICNIRP standards. Bending conditions and on-body measurements of the proposed antenna indicate that the antenna’s performance is unaffected. As a result, it is shown that the antenna possessed the ability to be utilized in WBAN applications.